Building Self-Esteem in the Early Years - Jenny Lukito Setiawan (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2005)
This article looks at the practical ways of building self-esteem in the early years. It describes the concepts of self-esteem and characteristics of children with high self-esteem and those with low self-esteem. The practical ways of building self-esteem are discussed under the five essential components of self-esteem pointed out by Reasoner and Dusa (1991), which include sense of security, identity, belonging, purpose, and personal competence.Key words: self-esteem, sense of security, sense of identity, sense of belonging, sense of purpose, sense of personal competence